Influence of quarry mining dust on PM2.5 in a city adjacent to a limestone quarry: Seasonal characteristics and source contributions - Peng, Xing; Shi, Guo-Liang; Zheng, Jun; Liu, Jia-Yuan; Shi, Xu-Rong; Xu, Jiao; Feng, Yin-Chang (The Science of the total environment, 2016)
To understand the influence of quarry mining dust on particulate matter, ambient PM2.5 and quarry mining dust source samples were collected in a city near quarry facilities during 2013–2014. Samples were subject to chemical analysis for dust-related species (Al, Si, Ca, Fe, Ti), tracer metals, carbon components and water-soluble ions. Seasonal variations of PM2.5 and its main chemical components were investigated. Distinctive seasonal variations of PM2.5 were observed, with the highest PM2.5 concentrations (112.42μgm−3) in fall and lowest concentrations in summer (45.64μgm−3). For dust-related species, mass fractions of Si and Al did not show obvious seasonal variations, whereas Ca presented higher fractions in spring and summer and lower fractions in fall and winter. A combined receptor model (PMF-CMB) was applied to quantify the quarry mining dust contribution to PM2.5. Seven sources were identified, including quarry mining dust, soil dust, cement dust, coal combustion vehicles, secondary sulfate and secondary nitrate. On a yearly average basis, the contribution of quarry mining dust to PM2.5 was 6%. The contribution of soil dust to PM2.5 was comparable with cement dust (13% and 13%, respectively). Other identified sources included vehicle, secondary sulfate, secondary nitrate and coal combustion, which contributed 23, 15, 9 and 18% of the total mass, respectively. Air mass residence time (AMRT) analysis showed that northeast and southeast regions might be the major PM2.5 source during the sampling campaign. The findings of this study can be used to understand the characteristics of quarry mining dust and control strategies for PM2.5. [Display omitted] •As a first effort, the influence of mineral dust on PM2.5 was investigated by employing the combined receptor model.•Reconstructed source contribution (RCSC) method was firstly established to estimate the performance of the model results.•Air mass residence time (AMRT) analysis was explored to investigate the regional influence on PM2.5.